Conversor CC-CA para aplicação em sistemas autônomos de energia elétrica - Bezerra, Luiz Daniel Santos (2010)
The study and development of new topologies or combinations of these in order to apply for autonomous systems of electric power supply are the main drivers of this work. The project consists of the combination of two converters, one high-gain step-up converter based on the three states switching cell whose role is to raise the battery voltage to a value of 400Vcc, thus forming a DC bus, and a single-phase inverter bridge-type with a LC filter, using the bipolar modulation type to obtain sinusoidal voltage similar to the power grid. The control of the high-gain converter is performed through a loop of current and voltage, both analog, but some part of the voltage loop is performed internally in a dsPIC, and inverter control is largely accomplished through this dsPIC (Digital modulator and controller), using the principles of discrete control. This system is capable of converting from 48V DC batteries in 220Vac and 60 Hz, with performance equal to or greater than 85% with a wide range of loading. Each stage has its theoretical study developed, and the introduction of a methodology for obtaining a reduced model of the high gain converter, and at the end, after the specifications and sizes are shown the experimental results of the prototype developed. The system was tested in various situations that can be found in everyday life, like starting a non- linear load, for example.